Flowers in the attic - Andrews, V. C. (Virginia C.) (New York : Pocket Books, 1979)
Four children are locked into the attic of their grandmother's home after the death of their father.
Adult.
Young Adult
Keywords: Child abuse -- Fiction; Grandmothers -- Fiction; Child abuse -- Fiction; Grandmothers -- Fiction